Aromatase Activity and Bone Loss in Men - Daniela Merlotti; Luigi Gennari; Konstantinos Stolakis; Ranuccio Nuti (Journal of Osteoporosis)
Aromatase is a specific component of the cytochrome P450 enzyme system responsible for the transformation of androgen precursors into estrogens. This enzyme is encoded by the CYP19A1 gene located at chromosome 15q21.2, that is, expressed in ovary and testis, but also in many extraglandular sites such as the placenta, brain, adipose tissue, and bone. The activity of aromatase regulates the concentrations of estrogens with endocrine, paracrine, and autocrine effects on target issues including bone. Importantly, extraglandular aromatization of circulating androgen precursors is the major source of estrogen in men. Clinical and experimental evidences clearly indicate that aromatase activity and estrogen production are necessary for longitudinal bone growth, the attainment of peak bone mass, pubertal growth spurt, epiphyseal closure, and normal bone remodeling in young individuals. Moreover, with aging, individual differences in aromatase activity may significantly affect bone loss and fracture risk in men.